The role of ethical leadership in enhancing exploitative and explorative learning simultaneously: what does it matter if employees view work as central?. Issue 2 (16th February 2021) - Ali, Moazzam; Qu, Yuanmei (Elly); Shafique, Shoaib; Pham, Nhat Tan; Usman, Muhammad
Abstract : Purpose: The present study aimed to test the hypothesis that ethical leadership positively contributes to exploitative learning and explorative learning simultaneously and then examine the moderating role of work centrality in the relationships of ethical leadership with exploitative learning and explorative learning. Design/methodology/approach: Time-lagged survey data were collected from 257 middle managers and their 257 immediate supervisors in 76 firms in China. Data were analyzed using structural equation modeling and Hayes' PROCESS macro for SPSS. Findings: The results revealed that ethical leadership positively contributed to exploitative learning and explorative learning simultaneously. Importantly, the authors found that work centrality strengthened the positive relationships of ethical leadership with both exploitative learning and explorative learning. Practical implications: The findings can help organizations enhance exploitative learning and explorative learning simultaneously and enable them to gain a sustainable competitive advantage. Originality/value: Although explorative learning and exploitative learning together constitute fundamental resources for organizations' long-term success, prior research has not looked into whether and when leader behaviors facilitate explorative learning and exploitative learning simultaneously. The study contributed to fill this gap by introducing ethical leadership, signifying its positive role in enhancing both explorative learning and exploitative learning, and establishing work centrality as a moderator to reinforce these two positive relationships.